Endogenous Technological Change and Wage Inequality - Lloyd-Ellis, Huw (American Economic Review, 1999)
Although microeconomic studies find a positive relationship between R&D and skill premia, much of the recent rise in U.S. wage inequality was accompanied by slowing labor-productivity growth and relatively slow introduction of new technologies. These conflicting observations are consistent with the effects of a skewed distribution of “absorptive capacities”—the rate at which technology-specific skills can be acquired—in a model of endogenous technological change. The framework is used to assess whether the productivity slowdown and the rise in wage inequality can be jointly accounted for by the contemporaneous decline in the growth rate of labor quality. (JEL E24, J31, O3)